2003
DOI: 10.1128/aac.47.8.2492-2498.2003
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for New Detection of Vancomycin-Resistant Enterococci in Acute-Care Hospitals That Employ Strict Infection Control Procedures

Abstract: Accurate assessment of the risk factors for colonization with vancomycin-resistant enterococci (VRE) among high-risk patients is often confounded by nosocomial VRE transmission. We undertook a 15-month prospective cohort study of adults admitted to high-risk units (hematology, renal, transplant, and intensive care) in three teaching hospitals that used identical strict infection control and isolation procedures for VRE to minimize nosocomial spread. Rectal swab specimens for culture were regularly obtained, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
67
4
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 32 publications
1
67
4
1
Order By: Relevance
“…This isolate was an E. faecium strain with vanA-type glycopeptide resistance. In contrast, the majority of VRE isolates in Australia today, in particular, E. faecium, possess vanB-type resistance (8,43). Following the first Australian case in 1994, VRE was soon reported in other Australian health care facilities, with outbreaks involving VRE colonization of the hospital environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This isolate was an E. faecium strain with vanA-type glycopeptide resistance. In contrast, the majority of VRE isolates in Australia today, in particular, E. faecium, possess vanB-type resistance (8,43). Following the first Australian case in 1994, VRE was soon reported in other Australian health care facilities, with outbreaks involving VRE colonization of the hospital environment.…”
mentioning
confidence: 99%
“…Following the first Australian case in 1994, VRE was soon reported in other Australian health care facilities, with outbreaks involving VRE colonization of the hospital environment. In the past decade, the rates of VRE and vancomycin-susceptible E. faecium (VSE) colonization and, to a lesser extent, infection have increased dramatically Australia-wide (32,33,43). A recent molecular epidemiological analysis of E. faecium bacteremia isolates at one Australian institution demonstrated that ST17 was the predominant MLST clone prior to 2005; however, this was subsequently replaced by a new clone, ST203, which was associated with a significant increase in episodes of bacteremia (32).…”
mentioning
confidence: 99%
“…The emergence of resistance to glycopeptide antibiotics (vancomycin and teicoplanin) in enterococci is one of the most serious infection control issues currently facing large hospitals in Australia, as elsewhere (13,20,24). There are currently six different vancomycin resistance (van) gene operons (vanA, -B, -C, -D, -E, and -G) mediating glycopeptide resistance.…”
mentioning
confidence: 99%
“…Inoculation of the media was in the reverse order for even-numbered specimens. The cultures were incubated at 35°C in ambient air and were examined daily, with cIDVRE incubated for 48 h, according to the manufacturer's recommendations (cIDVRE product insert; bioMérieux), and EVA plates were incubated for 72 h, as reported previously (13). Strains producing ␤-galactosidase (violet color) and ␤-glucosidase (blue-green color) on cIDVRE and esculin-positive isolates (black color) on EVA were considered possible E. faecium or E. faecalis isolates.…”
mentioning
confidence: 99%